IL-9 regulates intestinal barrier function in experimental T cell-mediated colitis - Gerlach, Katharina; McKenzie, Andrew N.; Neurath, Markus; Weigmann, Benno (Tissue Barriers, 2015)
As previous studies suggested that IL-9 may control intestinal barrier function, we tested the role of IL-9 in experimental T cell-mediated colitis induced by the hapten reagent 2,4,6-trinitrobenzenesulfonic acid (TNBS). The deficiency of IL-9 suppressed TNBS-induced colitis and led to lower numbers of PU.1 expressing T cells in the lamia propria, suggesting a regulatory role for Th9 cells in the experimental TNBS colitis model. Since IL-9 is known to functionally alter intestinal barrier function in colonic inflammation, we assessed the expression of tight junction molecules in intestinal epithelial cells of TNBS-inflamed mice. Therefore we made real-time PCR analyses for tight junction molecules in the inflamed colon from wild-type and IL-9 KO mice, immunofluorescent stainings and investigated the expression of junctional proteins directly in intestinal epithelial cells of TNBS-inflamed mice by Western blot studies. The results demonstrated that sealing proteins like occludin were up regulated in the colon of inflamed IL-9 KO mice. In contrast, the tight junction protein Claudin1 showed lower expression levels when IL-9 is absent. Surprisingly, the pore-forming molecule Claudin2 revealed equal expression in TNBS-treated wild-type and IL-9-deficient animals. These results illustrate the pleiotropic functions of IL-9 in changing intestinal permeability in experimental colitis. Thus, modulation of IL-9 function emerges as a new approach for regulating barrier function in intestinal inflammation.
EVALuna2:2009